Frat oncoproteins act at the crossroad of canonical and noncanonical Wnt-signaling pathways - van Amerongen, R; Nawijn, M.C; Lambooij, J.-P; Proost, N; Jonkers, J; Berns, A (Oncogene, 2010)
Wnt-signal transduction is critical for development and tissue homeostasis in a wide range of animal species and is frequently deregulated in human cancers. Members of the Frat/GBP family of glycogen synthase kinase 3β (Gsk3b)-binding oncoproteins are recognized as potent activators of the Wnt/β-catenin pathway in vertebrates. Here, we reveal a novel, Gsk3b-independent function of Frat converging on the activation of JNK and AP-1. Both these have been used as readouts for the noncanonical Frizzled/PCP pathway, which controls polarized cell movements and the establishment of tissue polarity. We find that Frat synergizes with Diversin, the mammalian homolog of the Drosophila PCP protein diego, in the activation of JNK/ AP-1 signaling. Importantly, Frat mutants deficient for binding to Gsk3b retain oncogenic activity in vivo, suggesting that Wnt/β-catenin-independent events contribute to Frat-induced malignant transformation. The observed activities of Frat are reminiscent of the dual function of Dishevelled in the Wnt/β-catenin and Frizzled/ PCP pathways and suggest that Frat may also function to bridge canonical and noncanonical Wnt pathways. Oncogene (2010) 29, 93-104; doi: 10.1038/onc.2009.310.; published online 5 October 2009 Keywords: Frat; Gsk3-binding protein; lymphomagenesis; Diversin; Wnt-signal transduction; planar cell polarity